Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

By covering hydrophobic nanomaterials on the high-nickel positive electrode active material, controlling the specific surface area and lithium carbonate content, the battery performance problems caused by the material's water absorption are solved, and higher capacity, magnification and cycling performance are achieved.

CN119297230APending Publication Date: 2025-01-10BEIJING EASPRING MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411376593.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

High-nickel positive electrode active materials tend to absorb water, resulting in an increase in the residual alkali content on the surface, reducing the battery circulation performance, and soft agglomeration between particles increases the material impedance, affecting the battery capacity and performance.

Method used

The positive electrode active material including a hydrophobic nanomaterial coating is used to control the specific surface area changes and lithium carbonate content, reduce the reaction between the material and air, reduce soft agglomeration between particles, and improve the hydrophobicity of the material and battery performance.

Benefits of technology

The capacity, magnification and cycling performance of the battery are improved, the consumption of active lithium and interface impedance are reduced, and the dynamic performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297230A_ABST
    Figure CN119297230A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode active material and a preparation method thereof, a positive electrode plate, a battery and electric equipment, the positive electrode active material comprises a substrate and a coating layer, the coating layer is located on at least part of the surface of the substrate, the coating layer comprises a hydrophobic nanometer material, the positive electrode active material meets the condition that BET (2)-BET (1) is larger than or equal to 0.03 m < 2 > / g and smaller than or equal to 0.15 m < 2 > / g, and the BET (1) is larger than or equal to 0.03 m < 2 > / g and smaller than or equal to 0.15 m < 2 > / g. BET (1) is the directly tested specific surface area of the positive electrode active material, and BET (2) is the specific surface area of the positive electrode active material after ultrasonic dispersion. Therefore, the positive electrode active material with good hydrophobicity and less soft agglomeration among particles is obtained, and a battery with relatively high capacity, excellent rate capability and cycle performance is further obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular, to positive electrode active materials and preparation methods thereof, positive electrode sheets, batteries, and electrical equipment. Background Art

[0002] Multi-material nickel cobalt manganese oxide Li[Ni x Co y Mn 1-x-y ]O2 has the advantages of high capacity and abundant resources, making it a more popular positive electrode active material in the market. Lithium nickel cobalt manganese oxide has a higher energy density, with a theoretical specific capacity of up to 280mAh / g and an energy density of up to 800Wh / kg. x Co y Mn 1-x-y ]O2, Ni is the main element contributing to the capacity. Ni element provides the electrons required for electrochemistry. Increasing the Ni content will significantly increase the capacity of the multi-material. The systems that have been studied more include low-nickel Li[Ni 1 / 3 Co 1 / 3 Mn 1 / 3 ]O2, Li[Ni 0.5 Co 0.2 Mn 0.3 ]O2, Li[Ni 0.6 Co 0.1 Mn 0.3 ]O2 and Li[Ni 0.6 Co 0.2 Mn 0.2 ]O2, and high nickel Li[Ni 0.8 Co 0.1 Mn 0.1 ]O2 system, etc. In order to have a higher specific capacity, the high nickel system (x>0.8) has been widely studied. Although high nickel materials have capacity advantages, the surface of high nickel materials easily absorbs water, resulting in an increase in the residual alkali content on the surface of high nickel materials, increasing the consumption of active lithium and reducing the cycle performance of the battery. In addition, after absorbing water, the particles are more likely to adhere to each other to form soft agglomerates, resulting in an increase in the ion transmission path during charging and discharging, an increase in material impedance, and is not conducive to the battery capacity and performance. Summary of the invention

[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.

[0004] The first aspect of the present application provides a positive electrode active material, the positive electrode active material comprising: a matrix, the matrix comprising Li 1+a Ni x Co y Mn z Am O2, wherein -0.1≤a≤0.1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2, 0≤m<0.1, A includes at least one of Al, Ti, Zr, Na, Sr, K, Ca, La, Ce, Pr, Nd, Ta, V, Rh, Ru, Ga, In, Y, Cu, Mg, Zn, Mo, Nb, Sb, P, Sn, W, Cl, F, and B; a coating layer, the coating layer is located on at least a portion of the surface of the substrate, the coating layer includes a hydrophobic nanomaterial, and the positive electrode active material satisfies: 0.03m 2 / g≤BET (2) -BET (1) ≤0.15m 2 / g, where BET (1) The specific surface area of ​​the positive electrode active material directly measured, BET (2) is the specific surface area of ​​the positive electrode active material after ultrasonic dispersion. (2) -BET (1) Within the above range, a positive electrode active material with good hydrophobicity and less soft agglomeration between particles is obtained. Good hydrophobicity can reduce the probability of the positive electrode active material reacting with CO2 and H2O in the air, reduce the content of residual alkali on the surface of the positive electrode active material, and improve the capacity and rate performance of the battery; less soft agglomeration between particles can make the electrolyte and the positive electrode active material particles fully contact during the battery cycle, reduce the impedance of the battery, and improve the cycle performance of the battery.

[0005] According to some embodiments of the present application, the positive electrode active material satisfies: 0.05m 2 / g≤BET (3) -BET (1) ≤0.25m 2 / g, where BET (3) The specific surface area of ​​the positive electrode active material after compaction and ultrasonic dispersion at a pressure of 5 T. Thus, by controlling the change rate of the specific surface area of ​​the positive electrode active material before and after compaction, a positive electrode active material with less soft agglomeration between particles and excellent hydrophobicity is obtained.

[0006] According to some embodiments of the present application, 0.4m 2 / g≤BET (1) ≤0.9m 2 / g.

[0007] According to some embodiments of the present application, the increase rate of the lithium carbonate content in the positive electrode active material is (LC1-LC0) / LC0×100%, and satisfies (LC1-LC0) / LC0×100%≤26%, optionally, (LC1-LC0) / LC0×100%≤20%, wherein LC0 is the content of lithium carbonate in the positive electrode active material after placing the positive electrode active material in an air environment with a dew point of -10°C for 0 hours, in units of ppm; LC1 is the content of lithium carbonate in the positive electrode active material after placing the positive electrode active material in an air environment with a dew point of -10°C for 24 hours, in units of ppm. As a result, the content of lithium carbonate that is not electrochemically active on the surface of the positive electrode active material is less, and the reduction of the dense layer of lithium carbonate can reduce the particle interface impedance and reduce the Li + The influence of diffusion can also reduce the consumption of active lithium and improve the capacity and rate performance of the material.

[0008] According to some embodiments of the present application, the increase rate of the lithium carbonate content in the positive electrode active material is (LC2-LC0) / LC0×100%, and satisfies (LC2-LC0) / LC0×100%≤38%, wherein LC2 is the content of the lithium carbonate in the positive electrode active material after the positive electrode active material is placed in an air environment with a dew point of -10°C for 48 hours, in ppm. As a result, the amount of lithium carbonate without electrochemical activity on the surface of the positive electrode material particles is reduced, and the consumption of active lithium is less, thereby improving the capacity and rate performance of the material.

[0009] According to some embodiments of the present application, the static contact angle of the positive electrode active material is θ and satisfies: θ ≥ 10°, optionally, 15° ≤ θ ≤ 30°. Thus, the hydrophobicity of the positive electrode active material is improved, the probability of the matrix reacting with CO2 and H2O is reduced, the content of lithium carbonate and lithium hydroxide that are not electrochemically active is reduced, and the consumption of active lithium is reduced, thereby improving the capacity and cycle performance of the battery.

[0010] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: 0.05 μm ≤ D50 (n) -D50 (w) ≤0.50μm, where D50 (n) D50 is the particle size corresponding to the particle size volume distribution percentage reaching 50% obtained by direct testing of the positive electrode active material. (w) The positive electrode active material is tested after ultrasonic dispersion, and the particle size volume distribution percentage obtained is 50% corresponding to the particle size; 0.15μm≤D50 (n) -D50 (y) ≤0.65μm, where D50 (y)The particle size corresponding to the volume distribution percentage of the obtained particle size reaches 50% by compacting with a pressure of 5T and then ultrasonically dispersing for testing. Therefore, by controlling the D50 of the positive electrode active material before and after ultrasound and before and after compaction, a positive electrode active material with less soft agglomeration between particles and excellent hydrophobicity is obtained.

[0011] According to some embodiments of the present application, D50 (n) 、D50 (w) 、D50 (y) Each independently ranges from 1.5 μm to 5 μm.

[0012] According to some embodiments of the present application, the hydrophobic nanomaterial comprises nanometal oxide, and at least a portion of the surface of the nanometal oxide is coated with the hydrophobic material, thereby forming a coating layer with good hydrophobicity and good conductivity on at least a portion of the surface of the substrate.

[0013] According to some embodiments of the present application, the positive electrode active material satisfies at least one of the following conditions: the nano metal oxide includes at least one of NiO, Ni2O, MgO, TiO2, CeO2, ZrO2, SiO2, ZnO, MnO2, Al2O3, Y2O3, WO3, Mg(OH)2, and Al(OH)3; the hydrophobic material includes at least one of hexamethyldisilazane, polydimethylsilazane, dimethylchlorosilane, octamethylcyclotetrasiloxane, stearic acid, and silicone oil.

[0014] The second aspect of the present application provides a method for preparing the positive electrode active material provided in the first aspect of the present application, the method comprising: mixing a Ni source, a Co source, a Mn source, an A source, and a Li source, sintering to obtain a matrix; mixing a nano hydrophobic material with the matrix, wherein the mass ratio of the hydrophobic nano material to the matrix is ​​n, and satisfies 0.00005≤n≤0.1, and drying to obtain the positive electrode active material. Thus, the positive electrode active material prepared by the method proposed in the present application has excellent hydrophobicity, can reduce the consumption of active lithium, and reduce the influence of CO2 and H2O in the air on the capacity of the positive electrode active material. At the same time, the present application directly mixes the hydrophobic nano material with the matrix by dry method, so that the hydrophobic nano material is coated on at least part of the surface of the matrix to form a protective layer, the process is simple, the environmental requirements are low, and the production cost can be reduced.

[0015] According to some embodiments of the present application, 0.0002≤n≤0.06. Thus, the hydrophobicity of the positive electrode active material is improved, and the content of residual alkali on the surface of the positive electrode active material is reduced.

[0016] According to some embodiments of the present application, the method further comprises: mixing the nano metal oxide and the hydrophobic material, heating at 200° C. to 900° C., and drying to obtain the nano hydrophobic material. Thus, a coating layer comprising the hydrophobic nano material is formed on at least part of the surface of the nano metal oxide, so that the hydrophobic nano material has excellent hydrophobicity and conductivity.

[0017] According to some embodiments of the present application, the drying temperature is 60° C.-250° C. Thus, the water content in the hydrophobic nanomaterial is reduced.

[0018] According to some embodiments of the present application, the mass ratio of the nano metal oxide to the hydrophobic material is 1:(0.001-0.3). Thus, a hydrophobic nano material with excellent hydrophobicity and conductivity is obtained.

[0019] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.

[0020] The fourth aspect of the present application provides a battery, comprising the positive electrode plate provided in the third aspect of the present application.

[0021] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0023] Figure 1 A schematic diagram of a process for preparing a positive electrode active material according to an embodiment of the present application is shown.

[0024] Figure 2 The SEM image of the positive electrode active material prepared in Example 3 of the present application is shown.

[0025] Figure 3 The mapping diagram of the Si element of the positive electrode active material prepared in Example 3 of the present application is shown.

[0026] Figure 4 The SEM image of the positive electrode active material prepared in Example 15 of the present application is shown.

[0027] Figure 5 The mapping diagram of the Ti element of the positive electrode active material prepared in Example 15 of the present application is shown.

[0028] Figure 6 The SEM image of the positive electrode active material prepared in Example 16 of the present application is shown.

[0029] Figure 7 The mapping diagram of the Al element of the positive electrode active material prepared in Example 16 of the present application is shown. DETAILED DESCRIPTION

[0030] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. If no specific techniques or conditions are specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0031] For multi-element cathode active materials in high nickel systems, spontaneous reactions will occur on the particle surface. 3+ Transformed into Ni 2+ , while releasing O 2- When the material is exposed to the air, the higher the nickel content, the easier it is for the material to absorb carbon dioxide and water in the air, and the following reactions are very likely to occur: 2- +CO2+H2O→CO3 2- +2OH - , Li + +CO3 2- +2OH - →Li2CO3+2LiOH, this reaction leads to the formation of Li2CO3 and LiOH on the surface of the material particles. The generated Li2CO3 and LiOH are not electrochemically active, and the dense Li2CO3 layer hinders Li + The diffusion of LiOH will cause the battery to produce gas during the charge and discharge process, resulting in battery bulging and other phenomena. LiOH will react with the lithium salt in the electrolyte to generate HF, causing the battery performance to deteriorate. The above reactions consume the active Li in the material. + Therefore, the capacity of the positive electrode active material decays significantly and the battery cycle performance decreases.

[0032] The first aspect of the present application provides a positive electrode active material, the positive electrode active material comprising: a matrix, the matrix comprising Li 1+a Ni x Co y Mn z A mO2, wherein -0.1≤a≤0.1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2, 0≤m<0.1, A includes at least one of Al, Ti, Zr, Na, Sr, K, Ca, La, Ce, Pr, Nd, Ta, V, Rh, Ru, Ga, In, Y, Cu, Mg, Zn, Mo, Nb, Sb, P, Sn, W, Cl, F, and B; a coating layer, the coating layer is located on at least a portion of the surface of the substrate, the coating layer includes a hydrophobic nanomaterial, and the positive electrode active material satisfies: 0.03m 2 / g≤BET (2) -BET (1) ≤0.15m 2 / g, where BET (1) The specific surface area of ​​the positive electrode active material directly measured, BET (2) is the specific surface area of ​​the positive electrode active material after ultrasonic dispersion.

[0033] Therefore, by using BET (2) -BET (1) Within the above range, a positive electrode active material with good hydrophobicity and less soft agglomeration between particles is obtained. Good hydrophobicity can reduce the probability of the positive electrode active material reacting with CO2 and H2O in the air, reduce the consumption of active lithium, reduce the content of residual alkali on the surface of the positive electrode active material, reduce the impact on lithium ion transmission, and improve the capacity and rate performance of the battery; there are fewer soft agglomerations between the particles, and during the battery cycle, the electrolyte and the positive electrode active material particles can be fully contacted, reducing the impedance of the battery, and improving the cycle performance of the battery, thereby obtaining a battery with higher capacity, excellent rate performance and cycle performance.

[0034] If BET (2) -BET (1) <0.03m 2 / g, although the specific surface area of ​​the positive electrode active material changes slightly before and after ultrasound, there will be more fine particles, which will aggravate the occurrence of side reactions and deteriorate the battery cycle performance; if BET (2) -BET (1) >0.15m 2 / g, indicating that there are many positive electrode active material particles clustered together. During the battery cycle, the electrolyte cannot fully contact with the positive electrode active material particles, and the battery impedance is large.

[0035] As an example, BET (2) -BET (1) Can be 0.03m 2 / g, 0.05m 2 / g, 0.07m 2 / g, 0.09m 2 / g, 0.1m 2 / g, 0.12m 2 / g, 0.15m 2 / g, etc., or may be within the range consisting of any of the above values.

[0036] In this application, BET (1) The test method is: 1g-8g of positive electrode active material is placed in a long glass tube for degassing, and then placed in a specific surface area meter for testing. The specific surface area of ​​the sample is obtained by testing in a nitrogen atmosphere using the principle of adsorption method, which is BET. (1) .BET (2) The test method is as follows: first, 1g-8g of positive electrode active material is dispersed by ultrasonic equipment, the ultrasonic frequency is 40kHz, and the ultrasonic time is 1min. Then, the sample is placed in a blast drying oven and dried at low temperature. Then, the sample is dried according to BET. (1) The specific surface area of ​​the sample is obtained by the test method, which is BET (2) .

[0037] According to some embodiments of the present application, 0.4m 2 / g≤BET (1) ≤0.9m 2 / g, for example, it can be 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, etc., or may be within the range consisting of any of the above values.

[0038] According to some embodiments of the present application, the positive electrode active material may satisfy: 0.05m 2 / g≤BET (3) -BET (1) ≤0.25m 2 / g, where BET (3) It is the specific surface area of ​​the positive electrode active material after compaction with a pressure of 5 T and then ultrasonic dispersion. The process of compacting the positive electrode material powder is used to identify the particle breakage during the preparation of the battery pole piece in advance, and by controlling the change rate of the specific surface area of ​​the positive electrode active material before and after compaction, a positive electrode active material with less soft agglomeration and particles that are not easy to break during battery preparation is obtained.

[0039] As an example, BET (3) -BET (1) Can be 0.05m 2 / g, 0.07m 2 / g, 0.09m 2 / g, 0.11m2 / g, 0.13m 2 / g, 0.15m 2 / g, 0.17m 2 / g, 0.19m 2 / g, 0.21m 2 / g, 0.23m 2 / g, 0.25m 2 / g, etc., or may be within the range consisting of any of the above values.

[0040] In this application, BET (3) The test method is as follows: first, 1g-8g of the positive electrode active material is compacted under a pressure of 5T, and then dispersed using an ultrasonic device with an ultrasonic frequency of 40kHz and an ultrasonic time of 1min. The sample is then placed in a blast drying oven for low-temperature drying, and finally the sample is subjected to BET (1) The specific surface area of ​​the sample is obtained by the test method, which is BET (3) .

[0041] According to some embodiments of the present application, the increase rate of the lithium carbonate content in the positive electrode active material is (LC1-LC0) / LC0×100%, and satisfies (LC1-LC0) / LC0×100%≤26%, wherein LC0 is the content of lithium carbonate in the positive electrode active material after the positive electrode active material is placed in an air environment at a dew point of -10°C for 0 hours, and the unit is ppm; LC1 is the content of lithium carbonate in the positive electrode active material after the positive electrode active material is placed in an air environment at a dew point of -10°C for 24 hours, and the unit is ppm. As an example, (LC1-LC0) / LC0×100% can be 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 20%, 23%, 26%, etc., or can be a range composed of any of the above values. According to some specific embodiments of the present application, (LC1-LC0) / LC0×100%≤20%. As a result, the content of lithium carbonate on the surface of the positive electrode active material is reduced, the interfacial impedance of the particles is reduced, and the lithium ion diffusion rate is increased. In addition, less lithium carbonate can also reduce the gas production of the battery during the charge and discharge process, and improve the battery's cycle performance and rate performance.

[0042] According to some embodiments of the present application, the increase rate of the lithium carbonate content in the positive electrode active material is (LC2-LC0) / LC0×100%, and satisfies (LC2-LC0) / LC0×100%≤38%, wherein LC2 is the content of the lithium carbonate in the positive electrode active material after placing the positive electrode active material in an air environment at a dew point of -10°C for 48 hours, in units of ppm. Thus, by controlling the increase rate of the lithium carbonate content in the positive electrode active material after 24 hours and 48 hours, a positive electrode active material with good hydrophobicity and more active lithium is obtained, thereby reducing the impact on the capacity of the positive electrode active material and improving the electrical performance.

[0043] As an example, (LC2-LC0) / LC0×100%≤30% can be 10%, 15%, 20%, 25%, 30%, 34%, 38%, etc., or can be a range consisting of any of the above values.

[0044] As an example, a may be -0.1, -0.05, 0, 0.05, 1, etc., or may be a range consisting of any of the above values.

[0045] As an example, x may be 0.8, 0.84, 0.88, 0.9, 0.92, 0.96 or 1, etc., or may be a range consisting of any of the above values.

[0046] As an example, y may be 0, 0.05, 0.1, 0.15 or 0.2, etc., or may be a range consisting of any of the above values.

[0047] As an example, z may be 0, 0.05, 0.1, 0.15 or 0.2, etc., or may be a range consisting of any of the above values.

[0048] As an example, m may be 0.02, 0.04, 0.06, 0.08, 0.1, etc., or may be a range consisting of any of the above values.

[0049] As an example, A may include at least one of Al, Ti, Zr, Sr, La, Ce, Pr, Ta, V, Y, Mg, Zn, Mo, Nb, Sb, Sn, W, and B.

[0050] According to some embodiments of the present application, the static contact angle of the positive electrode active material is θ and satisfies: θ≥10°, for example, it can be 10°, 12°, 14°, 16°, 18°, 20°, 25°, 30°, etc., or it can be a range composed of any of the above values. Thus, by making the static contact angle within the above range, the hydrophobicity of the positive electrode active material is improved, that is, the soft agglomeration between the particles is reduced, the risk of the particles not being able to fully contact the electrolyte is reduced, the generation of fresh surfaces during the charge and discharge process is reduced, the cycle performance is improved, and the content of lithium carbonate that is not electrochemically active produced by the reaction of the matrix with CO2 and H2O is reduced, the interface impedance is reduced, the lithium ion diffusion rate is increased, the kinetic performance is improved, and the capacity and rate performance of the battery are thereby improved.

[0051] According to some specific embodiments of the present application, 15°≤θ≤30°.

[0052] In this application, the static contact angle θ is the angle between the solid-liquid interface, the liquid interior and the gas-liquid interface at the interface of the solid, liquid and gas phases. The static contact angle θ mentioned in this application is directly measured by a contact angle meter. The test method is: the positive electrode active material powder sample is prepared into a sheet, and the shape of the liquid drop on the surface of the sheet sample is observed. After a tangent is made at the intersection of the solid and liquid phases, the angle measured by the protractor is θ.

[0053] According to some embodiments of the present application, 0.05 μm ≤ D50 (n) -D50 (w) ≤0.5μm, where D50 (n) D50 is the particle size corresponding to the particle size volume distribution percentage reaching 50% obtained by direct testing of the positive electrode active material. (w) The positive electrode active material is tested after ultrasonic dispersion, and the obtained particle size volume distribution percentage reaches the particle size corresponding to 50%. Therefore, ultrasound can disperse the bonded particles, and by controlling the D50 of the positive electrode active material before and after ultrasound within the above range, a positive electrode active material with less soft agglomeration between particles and excellent hydrophobicity is obtained.

[0054] As an example, D50 (n) -D50 (w) The thickness may be 0.05 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, etc., or may be within a range consisting of any of the above values.

[0055] In this application, the D50 of the positive electrode active material is tested. (n) When the prepared positive electrode active material powder is directly added to the laser particle size analyzer (DLS) for testing, the D50(n) Data; Test D50 of positive electrode active material (w) When the positive electrode active material to be tested is dispersed by ultrasonic equipment, the ultrasonic frequency is 40kHz, and the ultrasonic time is 1min. Then the sample is placed in DLS for testing to obtain D50 (w) data.

[0056] According to some embodiments of the present application, D50 (n) The thickness may be 2 μm to 5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., or may be within a range consisting of any of the above values.

[0057] According to some embodiments of the present application, D50 (w) The thickness may be 2 μm to 5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., or may be within a range consisting of any of the above values.

[0058] According to some embodiments of the present application, 0.15 μm ≤ D50 (n) -D50 (y) ≤0.65μm, where D50 (y) The particle size corresponding to the volume distribution percentage of the obtained particle size reaches 50% by compacting with a pressure of 5T and then ultrasonically dispersing for testing. Therefore, by controlling the D50 of the positive electrode active material before and after compaction, a positive electrode active material with less soft agglomeration between particles and excellent hydrophobicity is obtained.

[0059] As an example, D50 (n) -D50 (y) The thickness may be 0.15 μm, 0.25 μm, 0.35 μm, 0.45 μm, 0.55 μm, 0.65 μm, etc., or may be within a range consisting of any of the above values.

[0060] In this application, test D50 (y) When testing, first apply 5T pressure to the sample to reduce the soft space between particles, and then press the sample according to D50 (w) method to test.

[0061] According to some embodiments of the present application, D50 (y) The thickness may be 2 μm to 5 μm, for example, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, etc., or may be within a range consisting of any of the above values.

[0062] According to some embodiments of the present application, D50 (y) / BET (3) Can be 1μm·g / m2 -6μm·g / m 2 , for example, can be 1 μm·g / m 2 , 2μm·g / m 2 、3μm·g / m 2 , 4μm·g / m 2 , 5μm·g / m 2 , 6μm·g / m 2 The above-mentioned arbitrary numerical ranges may also be used.

[0063] According to some embodiments of the present application, the hydrophobic nanomaterial includes a nano metal oxide, and at least part of the surface of the nano metal oxide is coated with a hydrophobic material. Thus, the nano metal oxide is treated with a hydrophobic material to obtain a hydrophobic nanomaterial with good conductivity and good hydrophobicity, and the hydrophobic nanomaterial is coated on at least part of the surface of the substrate to form a coating layer with good hydrophobicity and good conductivity, thereby reducing the soft agglomeration of the particles and the content of lithium carbonate that is not electrochemically active, improving the full contact between the particles and the electrolyte, and also reducing the generation of fresh surfaces during the charge and discharge process, reducing the interface impedance, and improving the kinetic performance, thereby improving the capacity, rate performance and cycle performance of the battery.

[0064] According to some embodiments of the present application, the nano metal oxide may include at least one of NiO, Ni2O, MgO, TiO2, CeO2, ZrO2, SiO2, ZnO, MnO2, Al2O3, Y2O3, WO3, Mg(OH)2, and Al(OH)3.

[0065] According to some embodiments of the present application, the hydrophobic material includes at least one of hexamethyldisilazane (HMDS), polydimethylsilazane (PDMS), dimethylchlorosilane (DDS), octamethylcyclotetrasiloxane (D4), stearic acid, and silicone oil.

[0066] The second aspect of the present application provides a method for preparing the positive electrode active material provided in the first aspect of the present application, the method comprising: mixing a Ni source, a Co source, a Mn source, an A source, and a Li source, sintering to obtain a matrix; mixing a nano hydrophobic material with the matrix, the mass ratio of the hydrophobic nano material to the matrix is ​​n, and satisfies 0.00005≤n≤0.1, and drying to obtain the positive electrode active material. Thus, the positive electrode active material prepared by the method proposed in the present application has excellent hydrophobicity, and by forming a coating layer on at least part of the surface of the matrix, the direct contact between the matrix and the air can be reduced, the content of lithium carbonate can be reduced, the interface impedance can be improved, the kinetics can be improved, and the influence of CO2 and H2O in the air on the capacity and cycle performance of the positive electrode active material can be greatly reduced. At the same time, the present application directly mixes the hydrophobic nano material with the matrix by dry method, so that the hydrophobic nano material is coated on at least part of the surface of the matrix to form a protective layer, the process is simple, the environmental requirements are low, and the production cost can be reduced.

[0067] The method proposed in this application is described in detail below. Figure 1 , the method comprising:

[0068] S10: Mix Ni source, Co source, Mn source, A source and Li source, and sinter to obtain a matrix

[0069] According to some embodiments of the present application, the matrix material can be formed by a single sintering process. Specifically, a nickel-cobalt-manganese precursor, an A source, and a Li source are mixed and sintered to obtain a matrix.

[0070] According to some embodiments of the present application, the Ni source, Co source, Mn source, and Li source may be mixed and sintered first, and then mixed and sintered with the A source to form a matrix material. Specifically, the nickel-cobalt-manganese precursor and the Li source are mixed and sintered for the first time, and the sintered product is subjected to strong dissociation to obtain the process product G1; the process product G1 is mixed with the A source and sintered for the second time, and the sintered product is subjected to conventional dissociation and sieved to obtain the matrix material.

[0071] According to some embodiments of the present application, the specific process of the first sintering is: heating to temperature T1 at a first heating rate V1, keeping temperature for t1, heating to temperature T2 at a second heating rate V2, keeping temperature for t2, cooling to temperature T3 at a third rate V3, keeping temperature for t3, and finally cooling to room temperature.

[0072] As an example, V1 can be 3°C / min-8°C / min, for example, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc., or can be a range consisting of any of the above values.

[0073] As an example, T1 may be 400°C-750°C, for example, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, etc., or may be a range consisting of any of the above values.

[0074] As an example, V2 may be 2°C / min-5°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, etc., or may be a range consisting of any of the above values.

[0075] As an example, T2 may be 700°C-950°C, for example, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, etc., or may be a range consisting of any of the above values.

[0076] As an example, V3 may be 3°C / min-10°C / min, for example, 3°C / min, 5°C / min, 7°C / min, 9°C / min, 10°C / min, etc., or may be a range consisting of any of the above values.

[0077] As an example, T3 may be 500°C-750°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, etc., or may be a range consisting of any of the above numerical values.

[0078] As an example, t1:t2 may be (0-0.5):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc., or may be a range consisting of any of the above values.

[0079] As an example, t3:t2 may be (0-0.4):1, for example, 0.1:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, etc., or may be a range consisting of any of the above values.

[0080] Thus, by performing the first sintering under the above conditions, the electrochemical performance of the positive electrode active material is improved.

[0081] It should be noted that, when t1 is 0, the first sintering can be directly heated to T2 at V2; when t3 is 0, the first sintering can be directly cooled to room temperature at T2.

[0082] According to some embodiments of the present application, the equipment for the first sintering may be at least one of a roller kiln, a rotary kiln or a box furnace.

[0083] According to some embodiments of the present application, the atmosphere of the first sintering may be at least one of air, oxygen, and nitrogen.

[0084] According to some embodiments of the present application, strong dissociation refers to using a crushing device such as a jet mill and a rotary mill to perform a high-intensity and sufficient crushing treatment on the sintered product, and by adjusting the parameters of the crushing device, the D50 of the crushed sample is controlled. (n) And BET of samples before and after ultrasound (2) -BET (1)) Within a suitable range, the soft agglomeration between single crystal particles is reduced and the independence of single crystal particles is improved.

[0085] According to some embodiments of the present application, the specific process of the second sintering is: heating to temperature T4 at a fourth heating rate V4, keeping the temperature for a time t4, and then cooling to room temperature.

[0086] As an example, V4 can be 2°C / min-8°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc., or can be a range consisting of any of the above values.

[0087] As an example, T4 may be 650°C-780°C, for example, 650°C, 680°C, 710°C, 740°C, 780°C, etc., or may be a range consisting of any of the above values.

[0088] As an example, t4:t2 may be (0.5-1):1, for example, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc., or may be a range consisting of any of the above values.

[0089] Thus, by performing the second sintering under the above conditions, the electrochemical performance of the positive electrode active material is improved.

[0090] According to some embodiments of the present application, the equipment for the second sintering may be at least one of a roller kiln, a rotary kiln or a box furnace.

[0091] According to some embodiments of the present application, the atmosphere of the second sintering may be at least one of air, oxygen, and nitrogen.

[0092] According to some embodiments of the present application, conventional dissociation refers to crushing the sintered product using equipment such as a rotary mill and a colloid mill to reduce the soft agglomeration between single crystal particles and increase the independence of the particles.

[0093] According to some embodiments of the present application, the Ni source, Co source, Mn source, and Li source may be mixed and sintered first, and then mixed with the A source and sintered in stages to form a matrix material. Specifically, the nickel-cobalt-manganese precursor and the Li source are mixed and sintered for the first time, and the sintered product is subjected to strong dissociation to obtain a process product G1; the process product G1 is mixed with a portion of the A source and sintered for the second time, and the sintered product is subjected to conventional dissociation to obtain a process product G2; the process product G2 is mixed with another portion of the A source and sintered for the third time, and the sintered product is subjected to conventional dissociation to obtain a process product G3, which is sieved to obtain a matrix material.

[0094] The processes of the first sintering and the second sintering are not described in detail here.

[0095] According to some embodiments of the present application, the third sintering process may be: heating to temperature T5 at a fifth heating rate V5, keeping the temperature for a time t5, and then cooling to room temperature.

[0096] As an example, V5 can be 2°C / min-8°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc., or can be a range consisting of any of the above values.

[0097] As an example, T5 is 300°C-550°C, for example, it can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, etc., or can be a range consisting of any of the above values.

[0098] As an example, t5:t2 can be (0.3-1):1, for example, it can be 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc., or it can be a range consisting of any of the above values.

[0099] As an example, the nickel-cobalt-manganese precursor includes Ni x Co y Mn z (OH)2 or Ni x Co y Mn z At least one of O, wherein 0.8≤x≤1.0, 0≤y≤0.2, and 0≤z≤0.2.

[0100] As an example, the lithium source includes at least one of LiOH or Li2CO3.

[0101] According to some embodiments of the present application, the mesh size of the sieve used for sieving can be 100-600 mesh, for example, 100 mesh, 300 mesh, 600 mesh, etc., or can be a range composed of any of the above values. According to some specific embodiments of the present application, the mesh size of the sieve used for sieving can be 300-500 mesh.

[0102] S20: mixing the hydrophobic nanomaterial with the matrix, wherein the mass ratio of the hydrophobic nanomaterial to the matrix is ​​n and satisfies 0.00005≤n≤0.1, and drying to obtain the positive electrode active material

[0103] As an example, n can be 0.00005, 0.0001, 0.0002, 0.0005, 0.001, 0.005, 0.01, 0.05, 0.1, etc., or can be a range composed of any of the above values. According to some specific embodiments of the present application, 0.0002≤n≤0.06. Thus, the hydrophobicity of the positive electrode active material is improved, that is, the content of non-electrochemically active lithium carbonate on the surface of the material and the consumption of active lithium are reduced, and the soft agglomeration phenomenon between the particles is also improved, which is beneficial to the full contact between the particle surface and the electrolyte during the preparation of the battery slurry and the reduction of the fresh surface during the charge and discharge process.

[0104] If n<0.00005, the content of hydrophobic nanomaterials on the surface of the substrate is too little, and the improvement of the hydrophobicity of the positive electrode active material is poor; if n>0.1, the content of hydrophobic nanomaterials on the surface of the substrate is too much, and excessive hydrophobic nanomaterials will form in the gaps between the substrate particles, affecting the electrochemical properties of the positive electrode active material.

[0105] According to some embodiments of the present application, nano metal oxide and hydrophobic material are mixed, heated at 200° C.-900° C., and dried to obtain the nano hydrophobic material. Thus, a coating layer including the hydrophobic material is formed on at least part of the surface of the nano metal oxide, thereby obtaining a hydrophobic nano material with excellent hydrophobicity and conductivity.

[0106] The heating temperature of the nano metal oxide and the hydrophobic material can be 200° C., 400° C., 600° C., 800° C., 900° C., etc., or can be any range of the above values, thereby improving the coating effect of the hydrophobic material on the nano metal oxide.

[0107] According to some embodiments of the present application, the mass ratio of the nano metal oxide to the hydrophobic material can be 1:(0.001-0.3). For example, it can be 1:0.001, 1:0.01, 1:0.1, 1:0.2, 1:0.3, etc., or can be a range of any of the above values. Thus, a coating layer with good hydrophobicity and good conductivity is formed on at least part of the surface of the substrate.

[0108] According to some embodiments of the present application, the drying temperature is 60°C-250°C, for example, 60°C, 100°C, 150°C, 200°C, 250°C, etc., or any range of the above values. Thus, the water content in the hydrophobic nanomaterial is reduced.

[0109] According to some embodiments of the present application, the drying time can be 1h-14h, for example, can be 1h, 4h, 7h, 10h, 14h, etc., or can be a range composed of any of the above numerical values. Thus, the water content in the hydrophobic nano material is reduced. According to some specific embodiments of the present application, the drying time can be 3h-10h.

[0110] As an example, the drying equipment may include at least one of a kiln, a rotary kiln, a pusher kiln or a box furnace. The drying atmosphere may be at least one of air, oxygen, nitrogen and argon.

[0111] According to some embodiments of the present application, the equipment for mixing the hydrophobic nanomaterial with the matrix may include at least one of a high mixer, a plow or a ball mill, the mixing time may be 5 min-180 min, and the mixing speed may be 100 rpm-1200 rpm.

[0112] According to some embodiments of the present application, the average particle size of the nano-hydrophobic material can be 0.01μm-2.5μm, for example, it can be 0.01μm, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, etc., or it can be a range composed of any of the above numerical values.

[0113] In the present application, the test method for the average particle size of the nano-hydrophobic material is: the average value of the caliper diameters of more than 30 particles randomly selected under a scanning electron microscope (SEM), where the caliper diameter is equal to the average value of the length and width of the minimum circumscribed rectangle of a single particle.

[0114] According to some embodiments of the present application, the BET specific surface area of ​​the nano hydrophobic material is 5 m 2 / g-250m 2 / g, for example, it can be 5m 2 / g, 50m 2 / g、100m 2 / g, 150m 2 / g, 200m 2 / g, 250m 2 / g, etc., or may be within the range consisting of any of the above values.

[0115] In summary, the positive electrode active material proposed in this application has the following advantages:

[0116] (1) In the process of preparing the positive electrode active material, the present application controls the mass ratio of the hydrophobic nanomaterial and the matrix to obtain a positive electrode active material with good hydrophobicity and less soft agglomeration between particles. Good hydrophobicity can reduce the probability of the positive electrode active material reacting with CO2 and H2O in the air, reduce the consumption of active lithium, reduce the content of residual alkali on the surface of the positive electrode active material, reduce the impact on lithium ion transmission, and improve the capacity and rate performance of the battery; less soft agglomeration between particles can make the electrolyte and the positive electrode active material particles fully contact during the battery cycle, reduce the impedance of the battery, and improve the cycle performance of the battery, thereby obtaining a battery with high capacity, excellent rate performance and cycle performance.

[0117] (2) The increase rate of the lithium carbonate content in the positive electrode active material proposed in the present application is relatively low, indicating that the positive electrode active material has good hydrophobicity and consumes less active lithium. The positive electrode active material proposed in the present application can be used to obtain a battery with excellent cycle performance.

[0118] (3) The content of lithium carbonate on the surface of the positive electrode active material proposed in this application is relatively low, which can reduce the dense lithium carbonate layer on the surface of the positive electrode active material to Li + The influence of transmission, improves interface impedance, improves kinetics, and improves the gas production behavior of the battery during the charge and discharge process, thereby improving the battery's rate performance and cycle performance.

[0119] (4) The present application proposes a method for preparing positive electrode active materials. The base material and the hydrophobic nanomaterials are coated by a dry coating method, so that the hydrophobic nanomaterials can be evenly coated on the surface of the base material. Then, by low-temperature sintering, a hydrophobic multi-electrode active material can be obtained. The process is simple, the environmental requirements are low, and the production cost can be reduced.

[0120] The third aspect of the present application provides a positive electrode plate, comprising the positive electrode active material provided in the first aspect of the present application or the positive electrode active material prepared by the method provided in the second aspect of the present application.

[0121] The fourth aspect of the present application provides a battery, comprising the positive electrode sheet provided in the third aspect of the present application. Therefore, the battery provided in the present application has excellent cycle performance and rate performance.

[0122] The fifth aspect of the present application provides an electrical device, including the battery provided by the fourth aspect of the present application.

[0123] The embodiments of the present application are described in detail below. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific technology or conditions are indicated in the embodiments, the technology or conditions described in the document in this area or the product specification are used. The reagents used or the instruments that do not indicate the manufacturer are all conventional products that can be obtained commercially.

[0124] Example 1

[0125] 1. Preparation of positive electrode active materials

[0126] (1) LiOH, nickel-cobalt-manganese precursor Ni 0.95 Co 0.03 Mn 0.02 (OH)2 and ZrO2 were uniformly mixed in the ratio of n(Li):[n(Ni)+n(Co)+n(Mn)]:n(Zr)=1.03:1:0.002. In an oxygen atmosphere, the temperature was increased to 500°C at 5°C / min and kept for 1 hour. The temperature was then increased to 800°C at 3°C / min and kept for 8 hours. The temperature was then decreased to 650°C at 4°C / min and kept for 1 hour. Finally, the temperature was gradually decreased to room temperature. The sintered product was strongly dissociated using a rotary mill and a jet mill to obtain process product G1.

[0127] (2) The process product G1, CoOOH and Al2O3 were uniformly mixed in the ratio of [n(Ni)+n(Co)+n(Mn)]:n(Co):n(Al)=1:0.02:0.001, and the temperature was raised to 720°C at 5°C / min in an oxygen atmosphere, kept at that temperature for 6 h, and then gradually cooled to room temperature. The sintered product was dissociated using a colloid mill to obtain the process product G2.

[0128] (3) The process products G2, H3BO3 and WO3 were uniformly mixed in a ratio of [n(Ni)+n(Co)+n(Mn)]:n(B):n(W)=1:0.001:0.002, heated to 400°C at 6°C / min in an air atmosphere, kept at this temperature for 5 h, and then gradually cooled to room temperature. The sintered product was sieved to obtain the matrix material LiNi 0.93 Co 0.05 Mn 0.02 Zr 0.002 Al 0.001 B 0.001 W 0.002 O2.

[0129] (4) Nano-SiO2 and hydrophobic substance hexamethyldisilazane (HMDS) were mixed in a mass ratio of m (SiO2) :m (HMDS) =1:0.05, and react at 900°C for 1h to obtain a hydrophobic nanomaterial.

[0130] (5) The hydrophobic nanomaterial and the matrix material are mixed at a mass ratio of n=0.00005, and the mixture is dried at 120° C. for 6 h. After cooling, a hydrophobic multi-element positive electrode active material is obtained.

[0131] 2. Preparation of positive electrode sheet

[0132] The hydrophobic multi-element positive electrode active material, acetylene black and polyvinylidene fluoride (PVDF) were fully mixed with an appropriate amount of N-methylpyrrolidone (NMP) in a mass ratio of 95:3:2 to form a uniform slurry. The slurry was coated on an aluminum foil and dried at 120°C for 12 hours. It was then stamped at a pressure of 100 MPa to form a positive electrode sheet with a diameter of 11 mm and a thickness of 120 μm. The loading amount of the multi-element positive electrode material was 15 mg / cm 2 .

[0133] 3. Preparation of negative electrode sheet

[0134] The negative electrode uses a metal lithium sheet with a diameter of 15.6mm and a thickness of 0.45mm.

[0135] 4. Isolation film

[0136] A polyethylene porous membrane (Celgard 2325) having a thickness of 25 μm was used.

[0137] 5. Electrolyte

[0138] A mixture of equal volumes of ethylene carbonate (EC) and diethyl carbonate (DEC) with 1 mol / L LiPF6.

[0139] 6. Assemble the battery

[0140] After assembling the positive electrode sheet, separator, negative electrode sheet and electrolyte into a 2025 button cell, let it stand for 6 hours.

[0141] The preparation methods of the batteries in Examples 1 to 17 and Comparative Examples 1 to 3 are the same as those in Example 1, and the differences are detailed in Table 1.

[0142] Table 1

[0143]

[0144]

[0145] Performance Testing

[0146] 1. Lithium carbonate content test

[0147] Place 2g-6g of positive electrode active material in pure water and stir for 5 minutes. Then place the filtrate after filtration in an automatic positioning titrator and use dynamic titration method for testing. The test results can be used to obtain the lithium carbonate content through simple calculation.

[0148] 2. Specific surface area test

[0149] BET (1)The test method is: 1g-8g of positive electrode active material is placed in a long glass tube for degassing, and then placed in a specific surface area meter for testing. The specific surface area of ​​the sample is obtained by testing in a nitrogen atmosphere using the principle of adsorption method, which is BET. (1) .BET (2) The test method is as follows: first, 1g-8g of positive electrode active material is dispersed by ultrasonic equipment, the ultrasonic frequency is 40kHz, and the ultrasonic time is 1min. Then, the sample is placed in a blast drying oven and dried at low temperature. Then, the sample is dried according to BET. (1) The specific surface area of ​​the sample is obtained by the test method, which is BET (2) .BET (3) The test method is as follows: first, 1g-8g of the positive electrode active material is compacted under a pressure of 5T, and then dispersed using an ultrasonic device with an ultrasonic frequency of 40kHz and an ultrasonic time of 1min. The sample is then placed in a blast drying oven for low-temperature drying, and finally the sample is subjected to BET (1) The specific surface area of ​​the sample is obtained by the test method, which is BET (3) .

[0150] 3. Static contact angle test

[0151] The static contact angle θ mentioned in the present application is directly measured by a contact angle meter. The test method is: prepare the positive electrode active material powder sample into a sheet, observe the shape of the liquid drop on the surface of the sheet sample, make a cut at the intersection of the solid and liquid, and the angle measured by a protractor is θ.

[0152] 4.D50 test

[0153] The untreated or specially treated samples are placed in a laser particle size analyzer (DLS) for testing to obtain D50 data.

[0154] 5. Capacity and rate performance test

[0155] The charge and discharge voltage range was controlled to be 3.0V-4.3V. At room temperature, the button cell was charged and discharged twice at 0.1C, and then charged and discharged once at 0.2C, 0.33C, 0.5C and 1C respectively. The first 0.1C charge and discharge capacity was used to evaluate the first charge and discharge specific capacity and the first charge and discharge efficiency of the positive electrode active material. The rate performance of the multi-element positive electrode material was evaluated by the ratio of the 1C discharge specific capacity to the second 0.1C discharge specific capacity. Among them, the first 0.1C charge and discharge capacity is the discharge specific capacity of the button cell in the first cycle, the second 0.1C discharge specific capacity is the discharge specific capacity of the button cell in the second cycle, and the 1C discharge specific capacity is the discharge specific capacity of the button cell in the sixth cycle.

[0156] 6. Cycle performance test

[0157] The charge and discharge voltage range was controlled to be 3.0V-4.3V. At a constant temperature of 45°C, the button battery was charged and discharged twice at 0.1C, and then charged and discharged 80 times at 1C to evaluate the high-temperature capacity retention rate of the battery.

[0158] The test results of the positive electrode active materials in Examples 1 to 17 and Comparative Examples 1 to 3 are shown in Table 2.

[0159]

[0160]

[0161] The test results of the batteries in Examples 1 to 17 and Comparative Examples 1 to 3 are shown in Table 3.

[0162] Table 3

[0163]

[0164] It can be seen from the comparison between Examples 1 to 17 and Comparative Examples 1 to 3 that the battery proposed in this application has a higher first 0.1C discharge specific capacity, better rate performance, and higher cycle capacity retention rate, indicating that the battery proposed in this application has a higher first 0.1C discharge specific capacity, better rate performance, and higher cycle capacity retention rate by controlling BET (2) -BET (1) , which can reduce the probability of the positive electrode active material reacting with CO2 and H2O in the air to produce lithium carbonate, thereby reducing the consumption of active lithium. At the same time, there is less soft agglomeration between the positive electrode active material particles, and the electrolyte and the positive electrode active material can be in full contact, thereby improving the transmission of lithium ions.

[0165] It can be seen from the comparison between Examples 1 to 5 and Comparative Examples 1 to 3 that by controlling the content of the hydrophobic nanomaterial on the surface of the substrate (i.e., the ratio of the mass ratio of the hydrophobic nanomaterial to the substrate), the increase rate of the lithium carbonate content on the surface of the positive electrode active material, the change rate of the BET specific surface area of ​​the positive electrode active material after different treatments, the static contact angle, and the D 50 , and then obtain a positive electrode active material with good hydrophobicity and less lithium carbonate content on the substrate surface, thereby obtaining a battery with excellent discharge capacity, rate performance and cycle performance. It can be seen from Comparative Example 3 that when the content of hydrophobic nanomaterial on the substrate surface is too much, although the content of lithium carbonate on the surface of the positive electrode active material is less, the coating layer is thick, which is not conducive to lithium ion transmission, so the discharge capacity, rate performance and cycle performance of the battery will be reduced.

[0166] It can be seen from Examples 6 and 7 that after the hydrophobic nanomaterial is mixed with the matrix material and then dried at a relatively low temperature, a positive electrode active material having a coating layer on at least a portion of its surface can be obtained. The process is simple, the method is practical, and the operation is convenient. It can be completed on an existing multi-material production line, which can further reduce production costs.

[0167] It can be seen from Examples 8 to 12 that the nano-metal oxide and the hydrophobic material are mixed in different mass ratios and then mixed with the matrix material in the same mass ratio, which can also regulate the increase rate of the lithium carbonate content on the surface of the positive electrode active material, the change rate of the BET specific surface area of ​​the positive electrode active material after different treatments, the static contact angle, and the D 50 , thereby obtaining a positive electrode active material with good hydrophobicity and less lithium carbonate content on the matrix surface, thereby obtaining a battery with excellent discharge specific capacity, rate performance and cycle performance.

[0168] It can be seen from Examples 13 to 17 that by using different types of nano-metal oxides and hydrophobic materials to prepare hydrophobic nano-materials and then mixing them with a matrix material, a coating layer containing different hydrophobic nano-materials can be formed on the surface of the matrix, which can improve the hydrophobicity of the positive electrode active material and reduce the rate of increase of the lithium carbonate content of the positive electrode active material, thereby obtaining a battery with excellent discharge specific capacity, rate performance and cycle performance.

[0169] Figure 2 This is a SEM image of the positive electrode active material prepared in Example 3. It can be seen from the image that there is less softness between the particles of the positive electrode active material and the particle dispersion is better.

[0170] Figure 3 This is a mapping diagram of the positive electrode active material prepared in Example 3. It can be seen that the surface of the substrate has a uniformly distributed Si element.

[0171] Figure 4 This is a SEM image of the positive electrode active material prepared in Example 15. It can be seen from the image that there are fewer soft agglomerations between the positive electrode active material particles and the particle dispersion is better.

[0172] Figure 5 This is a mapping diagram of the positive electrode active material prepared in Example 15. It can be seen that the surface of the substrate has a uniformly distributed Ti element.

[0173] Figure 6 This is a SEM image of the positive electrode active material prepared in Example 16. It can be seen from the image that there are fewer soft agglomerations between the positive electrode active material particles and the particle dispersion is better.

[0174] Figure 7This is a mapping diagram of the positive electrode active material prepared in Example 16. It can be seen that the surface of the substrate has uniformly distributed Al elements.

[0175] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A positive electrode active material, characterized in that: include: A matrix comprising Li 1+a Ni x Co y Mn z A m O2, wherein -0.1≤a≤0.1, 0.8≤x≤1, 0≤y≤0.2, 0≤z≤0.2, 0≤m<0.1, and A includes at least one of Al, Ti, Zr, Na, Sr, K, Ca, La, Ce, Pr, Nd, Ta, V, Rh, Ru, Ga, In, Y, Cu, Mg, Zn, Mo, Nb, Sb, P, Sn, W, Cl, F, and B; The coating layer is located on at least part of the surface of the substrate, the coating layer includes a hydrophobic nanomaterial, and the positive electrode active material satisfies: 0.03m 2 / g≤BET (2) -BET (1) ≤0.15m 2 / g, where BET (1) The specific surface area of ​​the positive electrode active material directly measured, BET (2) is the specific surface area of ​​the positive electrode active material after ultrasonic dispersion.

2. The positive electrode active material according to claim 1, characterized in that The positive electrode active material meets the following requirements: 0.05m 2 / g≤BET (3) -BET (1) ≤0.25m 2 / g, where BET (3) It is the specific surface area of ​​the positive electrode active material after compaction with a pressure of 5T and ultrasonic dispersion.

3. The positive electrode active material according to claim 2, characterized in that 0.4m 2 / g≤BET (1) ≤0.9m 2 / g。 4. The positive electrode active material according to any one of claims 1 to 3, characterized in that: The increase rate of the lithium carbonate content in the positive electrode active material is (LC1-LC0) / LC0×100%, and satisfies (LC1-LC0) / LC0×100%≤26%, optionally, (LC1-LC0) / LC0×100%≤20%, wherein LC0 is the content of lithium carbonate in the positive electrode active material after placing the positive electrode active material in an air environment with a dew point of -10°C for 0 h, and the unit is ppm; LC1 is the content of lithium carbonate in the positive electrode active material after placing the positive electrode active material in an air environment with a dew point of -10°C for 24 h, and the unit is ppm.

5. The positive electrode active material according to claim 4, characterized in that The increase rate of the lithium carbonate content in the positive electrode active material is (LC2-LC0) / LC0×100%, and satisfies (LC2-LC0) / LC0×100%≤38%, wherein LC2 is the content of the lithium carbonate in the positive electrode active material after placing the positive electrode active material in an air environment with a dew point of -10°C for 48 hours, in ppm.

6. The positive electrode active material according to claim 5, characterized in that The static contact angle of the positive electrode active material is θ and satisfies: θ≥10°, optionally, 15°≤θ≤30°.

7. The positive electrode active material according to claim 6, characterized in that Satisfy at least one of the following conditions: 0.05μm≤D50 (n) -D50 (w) ≤0.5μm, where D50 (n) D50 is the particle size corresponding to the particle size volume distribution percentage reaching 50% obtained by direct testing of the positive electrode active material. (w) The positive electrode active material is tested after ultrasonic dispersion, and the particle size volume distribution percentage obtained is 50% corresponding to the particle size; 0.15μm≤D50 (n) -D50 (y) ≤0.65μm, where D50 (y) The particle size corresponding to the volume distribution percentage of 50% is obtained by compacting with a pressure of 5T and then ultrasonically dispersing for testing.

8. The positive electrode active material according to claim 7, characterized in that D50 (n) 、D50 (w) 、D50 (y) Each independently ranges from 1.5 μm to 5 μm.

9. The positive electrode active material according to claim 1, characterized in that The hydrophobic nano material comprises nano metal oxide, and at least a portion of the surface of the nano metal oxide is coated with a hydrophobic material.

10. The positive electrode active material according to claim 9, characterized in that Satisfy at least one of the following conditions: The nano metal oxide includes at least one of NiO, Ni2O, MgO, TiO2, CeO2, ZrO2, SiO2, ZnO, MnO2, Al2O3, Y2O3, WO3, Mg(OH)2, and Al(OH)3; The hydrophobic material includes at least one of hexamethyldisilazane, polydimethylsilazane, dimethylchlorosilane, octamethylcyclotetrasiloxane, stearic acid, and silicone oil.

11. A method for preparing the positive electrode active material according to any one of claims 1 to 10, characterized in that: include: A Ni source, a Co source, a Mn source, an A source, and a Li source are mixed and sintered to obtain a matrix; The hydrophobic nanometer material is mixed with the matrix, the mass ratio of the hydrophobic nanometer material to the matrix is ​​n, and 0.00005≤n≤0.1 is satisfied, and the mixture is dried to obtain the positive electrode active material.

12. The method according to claim 11, characterized in that 0.0002≤n≤0.06。 13. The method according to claim 11, characterized in that The method further comprises: The nano metal oxide and the hydrophobic material are mixed, heated at 200° C.-900° C., and dried to obtain the nano hydrophobic material.

14. The method according to claim 13, characterized in that The mass ratio of the nano metal oxide to the hydrophobic material is 1:(0.001-0.3).

15. The method according to claim 11, characterized in that The drying temperature is 60°C-250°C.

16. A positive electrode plate, characterized in that: The invention comprises the positive electrode active material according to any one of claims 1 to 10 or the positive electrode active material prepared by the method according to any one of claims 11 to 15.

17. A battery, characterized in that: Including the positive electrode sheet as described in claim 16.

18. An electrical equipment, characterized in that: Comprising the battery of claim 17.